Performance analysis of WMNs by WMN-GA simulation system for two WMN architectures and different TCP congestion-avoidance algorithms and client distributions. (2018) - Matsuo, Keita; Sakamoto, Shinji; Oda, Tetsuya; Barolli, Admir; Ikeda, Makoto; Barolli, Leonard
In this paper, we evaluate the performance of two wireless mesh networks (WMNs) architectures considering packet delivery ratio (PDR), throughput, delay and fairness index metrics. For simulations, we used ns-3, distributed coordination function (DCF) and optimised link state routing (OLSR). We compare the performance of transmission control protocol (TCP) Tahoe, Reno and NewReno for normal and uniform distributions of mesh clients by sending multiple constant bit rate (CBR) flows in the network. The simulation results show that the PDR for both distributions and architectures is almost the same, but the PDR of I/B WMN for uniform distribution is a little bit higher than normal distribution. For both WMN architectures, the throughput of normal distribution is better than uniform distribution. The delay of Tahoe is a little bit lower compared with other algorithms for normal distribution and Hybrid WMN, but in case of uniform distribution, the NewReno performs better than other algorithms for both architectures. The fairness index of normal distribution is higher than uniform distribution.